Low expression of hsa_circ_0006633 in human gastric cancer and its clinical significances - Rongdan Lu; Yongfu Shao; Guoliang Ye; Bingxiu Xiao; Junming Guo (Tumor Biology, 2017)
Circular RNAs are new type of endogenous RNAs, which play an important role in the regulation of gene expression and indicate a great capacity in clinical diagnosis and treatments of diseases. However, the role of circular RNAs in gastric cancer remains unknown. In this study, we chose hsa_circ_0006633 as the target circular RNA and measured its levels in human gastric cancer tissues, plasma, and gastric cell lines by real-time quantitative reverse transcription polymerase chain reaction. Hsa_circ_0006633 levels at multiple stages of gastric tumorigenesis were then explored, and its relationships with clinicopathological features were analyzed as well. We found that the expression levels of hsa_circ_0006633 in four gastric cancer cell lines, HGC-27, SGC-7901, MGC-803, and AGS, were downregulated than those in normal gastric mucosal epithelial cell line GES-1. Then, we further detected that it was downregulated in 79.2% (76/96) gastric cancer tissues compared with the adjacent non-tumorous tissues. The lower expression of hsa_circ_0006633 was associated with cancer distal metastasis ( p  = 0.037) and tissue carcinoembryonic antigen level ( p  = 0.041). In addition, hsa_circ_0006633 expression was significantly decreased in gastritis and dysplasia tissues comparing with the healthy control. Moreover, plasma hsa_circ_0006633 levels were significantly increased in gastric cancer compared with healthy control. Our data imply that hsa_circ_0006633 may play an important role in gastric carcinogenesis and is also a potential biomarker for screening gastric cancer.